BioBlitzed: The first record of Brachyponera chinensis (Emery, 1895) in Germany (Hymenoptera: Formicidae) - Boudinot, Brendon E.; Palm, Benjamin; Bellersheim, Aron; Richter, Adrian; Grunicke, David; Härtel, Max P.; Haas-Renninger, Maura (Zootaxa, 2026)
We report the first confirmed occurrence in Germany of the Asian needle ant, Brachyponera chinensis (Emery, 1895), from a complete outdoor colony collected in the Rosensteinpark of Stuttgart during a BioBlitz on 2 June 2025. Based on additional records from Rosensteinpark, it appears that this may be an established local population, capable of surviving over winter, in contrast to other, incidental occurrences in the country. Brachyponera chinensis is native to East Asia and is known as both an ecologically disruptive invasive in parts of the southeastern United States and as a species of medical concern due to allergic reactions from their stings. To aid in morphology-based identification, we refine the diagnosis of this species relative to close congeners. Our record, verified by voucher specimens and morphological comparison, represents a potential early-stage introduction of B. chinensis into Central Europe. The species was likely introduced to the Rosensteinpark through horticultural specimen transfer, as the park includes the zoological-botanical garden Wilhelma. The finding raises questions about possible urban establishment and future spread and emphasizes the need for ongoing monitoring of the ant fauna in Germany.